Inclusive Education: 'from West To The Rest' (Grech 2011, 88) - About The Need Of Getting Aware Of Knowledge (In-)Equity & Open Science - Kruschick, Felicitas (My University, 2021)
The presentation was part of the Ignition Talk I held during the online-based Open Science Barcamp on 16th February 2021. For more information recommend the Blogpost about the Ignition Talk: https://waytodif.hypotheses.org/84
Keywords: Power Dynamics; Open Science; Inclusive Education